2015
DOI: 10.1016/j.ajog.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Timing of treatment initiation for mild gestational diabetes mellitus and perinatal outcomes

Abstract: Objective To examine the association between gestational age (GA) at the time of treatment initiation for gestational diabetes (GDM) and maternal and perinatal outcomes. Study Design A secondary analysis of a multicenter randomized treatment trial of mild GDM in which women with mild GDM were randomized to treatment versus usual care. The primary outcome of the original trial, as well as this analysis, was a composite perinatal adverse outcome that included neonatal hypoglycemia, hyperbilirubinemia, hyperins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
0
19
1
Order By: Relevance
“…Interestingly, the effect of treatment on perinatal outcomes, including a composite of neonatal hypoglycemia, hyperbilirubinemia, hyperinsulinemia, and birth trauma, did not vary by the gestational age of initiation of mild GDM treatment, which ranged from 24 to 31 weeks of gestation. 14 This finding however may not be generalizable to women with more severe forms of GDM. 14 The treatment effect on fetal overgrowth did vary according to neonatal sex, with a significant treatment reduction in birthweight percentile and neonatal fat mass observed in the males but not the females.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the effect of treatment on perinatal outcomes, including a composite of neonatal hypoglycemia, hyperbilirubinemia, hyperinsulinemia, and birth trauma, did not vary by the gestational age of initiation of mild GDM treatment, which ranged from 24 to 31 weeks of gestation. 14 This finding however may not be generalizable to women with more severe forms of GDM. 14 The treatment effect on fetal overgrowth did vary according to neonatal sex, with a significant treatment reduction in birthweight percentile and neonatal fat mass observed in the males but not the females.…”
mentioning
confidence: 93%
“…14 This finding however may not be generalizable to women with more severe forms of GDM. 14 The treatment effect on fetal overgrowth did vary according to neonatal sex, with a significant treatment reduction in birthweight percentile and neonatal fat mass observed in the males but not the females. 15 One explanation hypothesized for these findings was that there may be gender differences in susceptibility to oxidative stress or in the response to a treatment that might mitigate oxidative stress, however markers of oxidative stress were not measured to evaluate this hypothesis.…”
mentioning
confidence: 93%
“…Accumulated studies have shown that pregnancy complications, such as pregnancy-induced hypertension (PIH), gestational diabetes mellitus (GDM) and intrahepatic cholestasis (ICP), could affect perinatal situations [7][8][9][10][11][12][13]. Glucose plays important roles in brain metabolism and brain development in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…In late‐onset GDM, we found that there was insignificant higher cesarean section rate (41.9% vs 25.0%, P = 0.210) and more large for gestational age (LGA) (7.0% vs 2.1%, P = 0.429). Palatnik et al . and Black et al .…”
Section: Discussionmentioning
confidence: 98%